THE ROLE OF THE JADID MOVEMENT IN RAISING NATIONAL SPIRITUALITY - Kurbanova Shakhnoza Umarbaevna; Normatov Otabek Makhamatjonovich (Web of Journals Publishing, 2025)
The article examines the general content of the Jadid movement and its role in raising the spirituality of the people. In particular, there were also meaningful comments on the instructive teachings of our scientists and educators who worked in the past.
Keywords: Jadid, enlightenment, Jadidism, spiritual heritage, spirituality, science, education.